2002
DOI: 10.1021/bi011166v
|View full text |Cite
|
Sign up to set email alerts
|

The Different Folding Behavior of Insulin and Insulin-like Growth Factor 1 Is Mainly Controlled by Their B-Chain/Domain

Abstract: Although insulin and insulin-like growth factor 1 (IGF-1) share homologous sequence, similar tertiary structure, weakly overlapped biological activity, and a common ancestor, the two highly homologous sequences encode different folding behavior: insulin folds into one unique stable tertiary structure while IGF-1 folds into two disulfide isomers with similar thermodynamic stability. To further elucidate the molecular mechanism of their different folding behavior, we prepared two single-chain hybrids of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 53 publications
3
47
0
Order By: Relevance
“…It is the different disulfide pairing that results in the different retention time of peak B of isomer 1 and peak C of isomer 2. Together with the result of CD analysis, the folding behavior of IGF-1/mini-IGF-1 (37), and the results of ILP and its mutants (40,41), it can reasonably be presumed that the disulfides of isomer 2 are identical to those of insulin/ native IGF-1, while the disulfides of isomer 1 are identical to those of swap IGF-1. Moreover, all of the three major fragments of [pE]ILP have the expected molecular masses; therefore, the different molecular masses between ILP and [pE]ILP must be caused by the difference of the three N-terminal residues, Gln-Ala-Glu.…”
Section: Peptide Mapping Of the Disulfide Isomers Of Ilp And [Pe]-ilpmentioning
confidence: 82%
See 1 more Smart Citation
“…It is the different disulfide pairing that results in the different retention time of peak B of isomer 1 and peak C of isomer 2. Together with the result of CD analysis, the folding behavior of IGF-1/mini-IGF-1 (37), and the results of ILP and its mutants (40,41), it can reasonably be presumed that the disulfides of isomer 2 are identical to those of insulin/ native IGF-1, while the disulfides of isomer 1 are identical to those of swap IGF-1. Moreover, all of the three major fragments of [pE]ILP have the expected molecular masses; therefore, the different molecular masses between ILP and [pE]ILP must be caused by the difference of the three N-terminal residues, Gln-Ala-Glu.…”
Section: Peptide Mapping Of the Disulfide Isomers Of Ilp And [Pe]-ilpmentioning
confidence: 82%
“…The different folding behavior of insulin/PIP and IGF-1 is mainly controlled by their B-chain/domain that controls the different energetic state of the intra-A-chain/domain disulfide (37,38).…”
mentioning
confidence: 99%
“…Our previous results demonstrated that the different folding behavior of insulin and IGF-1 is mainly controlled by their B-chain/domains (24,26) (28). They proposed that the N-terminal extension imparts a steric constraint at a crucial point in folding, thus allowing native disulfide bonds to form efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Mini-IGF-1 (the C-terminus of IGF-1 B-domain and the N-terminus of IGF-1 A-domain were linked together by a dipeptide, Ala-Lys, and B30Thr was also replaced by Lys) has bifurcating folding behavior similar to that of IGF-1 (24). Previously, on the basis of studies of folding behavior of mini-IGF-1, PIP, and hybrids Ins(A)/IGF-1(B) and Ins(B)/ IGF-1(A), we have demonstrated that the different folding behavior of insulin/PIP and IGF-1/mini-IGF-1 is mainly controlled by their B-chain/domains (24). The different energetic states of the intra-A-chain/domain disulfide (14,25), which had been suggested to correspond to the different folding behavior of insulin and IGF-1, are also controlled by their B-chain/domains (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation